RESULTS OF QUALITY COMPREHENSIVE EVALUATION OF DENTAL CARE FOR CHILDREN WITH BLOOD CLOTTING (PATHOLOGY) - M. A. Gavrilenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
Background. Treatment methods for diseases of teeth hard tissues and periodontium for children with blood clotting pathology are described in modern literature. But in practice we are faced with the problem of providing dental treatment for these children. Work of pediatric dentist is prevented by the risk of bleeding, fear of dental procedures, child’s psychoemotional tension and refusal of treatment because of bleeding. Taking into account the specificity of blood clotting pathology, surgical methods of dental treatment prevail for these children, which is evidenced by the early loss of deciduous and permanent teeth, occlusal surface disturbances, dentoalveolar anomalies, inflammatory diseases of periodontal tissues.